Interpretasi Bawah Permukaan Dengan Metode Self Potential Daerah Bledug Kuwu Kradenan Grobogan - Dwi Indriana, Rina; Nurwidyanto, M. Irham; W. Haryono, Kurnia (BERKALA FISIKA, 2007)
The geophysics research to observe the subsurface anomaly in Bledug Kuwu had been done. It was used to analyze and interpret the potential data. The purpose of this research was to interpret the object of subsurface anomaly. The research was used self potential method with base point electrode configuration. Data processed used Surfer 8 software, which result was an isopotential contour map. The modeling processed used curve matching for a spherical model. By using Bhattacharya theory, the depth and polarization angle was founded as the parameter of a spherical model. The researchâ€™s result of the depth of anomaly origin is 19,5 m, 23,68m, and 40,8 m. The polarization angle is 70o, 70,38o and 100o. Â Keywords: Bledug Kuwu, self potential, spherical model Â